2021
DOI: 10.3390/nu13113684
|View full text |Cite
|
Sign up to set email alerts
|

A High-Sodium Diet Modulates the Immune Response of Food Allergy in a Murine Model

Abstract: Mounting evidence demonstrates that a high-salt diet (HSD) not only affects hemodynamic changes but also disrupts immune homeostasis. The T helper 17 (Th17) and regulatory T cells (Tregs) are susceptible to hypersalinity. However, research on the influence of sodium on Th2-mediated food allergies remains scarce. We aimed to investigate the effect of dietary sodium on the immune response to food allergies. Mice maintained on an HSD (4% NaCl), low-salt diet (LSD; 0.4% NaCl), or control diet (CTRL; 1.0% NaCl) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These effects were dependent on NFAT5 and SGK1. 65 Consistently, an HSD augmented Th2 responses in food allergy mice, 136 while the high-salt formulation of Al(OH) 3 enhanced the ovalbumin (OVA)induced Th2 response in mice. 109 In addition, high NaCl can significantly increase the polarization of human Tfh cells.…”
Section: Other T Helper Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…These effects were dependent on NFAT5 and SGK1. 65 Consistently, an HSD augmented Th2 responses in food allergy mice, 136 while the high-salt formulation of Al(OH) 3 enhanced the ovalbumin (OVA)induced Th2 response in mice. 109 In addition, high NaCl can significantly increase the polarization of human Tfh cells.…”
Section: Other T Helper Cellsmentioning
confidence: 90%
“…These responses were associated with Th17 cell activation in the kidney. 163,164 Moreover, an HSD might exacerbate food allergy in mice, 136 while sodium may participate in the progression of atopic dermatitis by regulating Th2 responses. 65…”
Section: Othersmentioning
confidence: 99%
“…Studies found that inhibiting the entry of Ca 2+ through calcium channels can stabilize mast cells, to play a protective role against ovalbumin (OVA)-sensitized food allergies . In the mouse model of food allergies, excessive intake of Na + can promote Th2 response . Selenium-enriched foods have gained popularity in recent years, and selenium has also been shown to be involved in multiple processes of food allergies, including maintenance of immune homeostasis, prevention of free radical damage, and modulation of the gut microbiota, all of which may help prevent and treat food allergies .…”
Section: Direct Intervention and Modulation Of Food Allergies By Matr...mentioning
confidence: 99%
“…30 In the mouse model of food allergies, excessive intake of Na + can promote Th2 response. 31 Selenium-enriched foods have gained popularity in recent years, and selenium has also been shown to be involved in multiple processes of food allergies, including maintenance of immune homeostasis, prevention of free radical damage, and modulation of the gut microbiota, all of which may help prevent and treat food allergies. 32 It is not hard to see from these studies that the effects of the large family of minerals that are members of food allergies cannot be overstated.…”
Section: As Antigens or Immunomodulatorymentioning
confidence: 99%